E-228 Meningiomas presenting with spontaneous intracranial hemorrhage: a case series. (23rd July 2022) - Alwakeal, A; Klein, J; Winterhalter, E; Jahromi, B; Potts, M
Abstract : Background: Spontaneous intracranial hemorrhage is a rare presentation of meningioma. We sought to review our experience with this rare presentation. Methods: We conducted a retrospective review of pathologically proven meningioma cases at our institution between 2001 and 2020 to identify cases that presented with intracranial hemorrhage. Patient demographics, imaging findings, treatments, and outcomes were recorded. Results: We identified four patients who presented with spontaneous (non-traumatic) intracranial hemorrhage attributed to a meningioma. Patient ages ranged from 36–82 years and two were female. Three patients had a history of hypertension and two were on anticoagulation medications at the time of presentation. Two patients presented with intraparenchymal hemorrhages, one with a subdural hemorrhage, and one with subarachnoid hemorrhage. All hemorrhages were adjacent to the respective meningiomas. Meningioma locations included convexity in three patients and sphenoid wing in one. All patients underwent successful surgical resection of the meningioma. Pathology results revealed grade I meningiothelial meningioma in two patients and atypical grade II characteristics in the other two patients. Additionally, the KI-67 and mitotic figure were highly varied, ranging from 1–30% and 0–10%, respectively. There was no tumor recurrence during follow-up periods ranging from 5–26 months. Conclusion: Meningioma is a rare cause of spontaneous intracranial hemorrhage and should be considered in the workup of intracranial hemorrhage. Disclosures: A. Alwakeal: None. J. Klein: None. E. Winterhalter: None. B. Jahromi: None. M. Potts: None.